2006
DOI: 10.1002/rcm.2498
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the properties of internal standards for quantitative matrix‐assisted laser desorption/ionization mass spectrometry of small molecules

Abstract: Growing interest in the ability to conduct quantitative assays for small molecules by matrix-assisted laser desorption/ionization (MALDI) has been the driving force for several recent studies. This present work includes the investigation of internal standards for these analyses using a high-repetition rate MALDI triple quadrupole instrument. Certain physicochemical properties are assessed for predicting possible matches for internal standards for different small molecules. The importance of similar molecular w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
83
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(87 citation statements)
references
References 27 publications
(45 reference statements)
3
83
1
Order By: Relevance
“…substitution of aspartic acid for glutamic acid or alanine for glycine) and these have been shown to compensate for crystallization irregularities and subsequent desorption and gas phase effects. The importance of a vicinal mass for the internal standard has also been reported based on experiments with a series of acylcarnitines having a fixed charge site and growing alkyl chain length [21]. In the final analysis, however, the acceptable degree of difference between the internal standard and the analyte is often only determined by experimentation and must be viewed in the context of the analytical objective.…”
Section: The Internal Standardmentioning
confidence: 99%
See 1 more Smart Citation
“…substitution of aspartic acid for glutamic acid or alanine for glycine) and these have been shown to compensate for crystallization irregularities and subsequent desorption and gas phase effects. The importance of a vicinal mass for the internal standard has also been reported based on experiments with a series of acylcarnitines having a fixed charge site and growing alkyl chain length [21]. In the final analysis, however, the acceptable degree of difference between the internal standard and the analyte is often only determined by experimentation and must be viewed in the context of the analytical objective.…”
Section: The Internal Standardmentioning
confidence: 99%
“…Results for the quantification of small molecules with molecular masses <500 Da by MALDI were generally good. In a companion study, the same authors focused their attention on the selection of internal standards for low mass quantification by MALDI and discussed the importance of a vicinal mass for the internal standard [21]. Both these studies were performed on a prototype MALDI-triple quadrupole instrument equipped with a high repetition rate laser.…”
Section: Low Molecular Mass Analytesmentioning
confidence: 99%
“…The above experiment was repeated on the five COC/COC-d 3 solutions, except that no CID voltage was applied so that the ions at m/z 304 and 307 were isolated but not fragmented. The ratio of intensities of m/z 304 to 307 was then monitored for different isolation window widths (4,6,and 8 Da). Results showed that the signal ratio of m/z 304 to 307 remained approximately equal to 1 for concentrations 0.12-2.0 g/mL for isolation widths of 6 and 8 Da; however, the signal ratio steadily increased for a 4 Da isolation window at concentrations above 0.50 g/mL.…”
Section: Isolation Window Width and Automatic Gain Controlmentioning
confidence: 99%
“…Laser power can also be optimized along with choice of matrix compound to maximize analyte signal while avoiding space-charge effects. The use of internal standards for quantitative MALDI-MS has been shown to improve signal stability, if the solution-phase properties are carefully matched as in an isotopic standard [6].…”
mentioning
confidence: 99%
“…Matrix-assisted laser desorption/ionization time-of-ight/time-of-ight mass spectrometry (MALDI-TOF/TOF MS) has potentials to be applied to the quali cation and quanti cation of small molecules. [11][12][13][14] It can avoid the need for LC separation prior to MS analysis, resulting in reduction of turn-around time. Moreover, it can allow quick assessment of result quality by identifying interfering signal peaks near the target analyte in the entire MS and/or MS/MS spectra.…”
Section: Introductionmentioning
confidence: 99%